2011
DOI: 10.3855/jidc.2177
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum malaria, bilateral sixth cranial nerve palsy and delayed cerebellar ataxia

Abstract: We describe the case of a 14-year-old Caucasian male, a resident in the Democratic Republic of the Congo, who was observed in Portugal with severe Plasmodium falciparum malaria with high-level parasitemia and severe thrombocytopenia. The course was complicated by bilateral sixth cranial nerve palsy during acute malaria, followed by the appearance of delayed cerebellar ataxia during the recovery phase. This occurred after successful treatment with quinine plus doxycycline over seven days. Different levels of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Although psychiatric symptoms are only rarely associated with delayed cerebellar syndromes in the literature, when reported, these have included giddiness [ 56 ], alterations in attention [ 60 ], and word-finding difficulties [ 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although psychiatric symptoms are only rarely associated with delayed cerebellar syndromes in the literature, when reported, these have included giddiness [ 56 ], alterations in attention [ 60 ], and word-finding difficulties [ 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral sixth cranial nerve palsy due to Plasmodium falciparum malaria has been reported in a 14-year child. 7 Bell's palsy is a facial nerve palsy involving the lower motor neuron. Bell's palsy results in weakness of facial muscles.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that malaria parasite may damage the peripheral nerves by vascular occlusion, thus causing anoxic stagnation in the vasa nervosum, which may lead to temporary demyelination and recovery after disappearance of the parasitemia and establishment of normal blood flow in the vasa nervosum [8]. In malaria, asexual-stage infections are accompanied by the release of cytokines and other immunological mediators that may mimic Guillain-Barre syndrome [9,13]. It is likely that these immunological mediators may have caused demyelination in the index patient giving rise to Gullain-Barre like syndrome affecting only the facial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery of facial paralysis due to Bell's palsy begins within three weeks of onset of the illness with complete recovery occurring within three to six months [7]. Sim et al, [8] reported facial diplegia in a 20 year old boy infected with Plasmodium vivax in Korea while Duque et al, [9] reported bilateral 6 th cranial nerve palsy caused by P. falciparum in a 14 year old Caucasian living in Democratic Republic of Congo. Haematological response to malaria infection has been documented.…”
Section: Introductionmentioning
confidence: 99%